REVEALING THE MEANING OF THE REGISTER IN A COMMUNITY OF JOURNALIST IN MALANG RAYA: MENGUNGKAP MAKNA REGISTER PADA KELOMPOK JURNALIS DI MALANG RAYA - Wilda Fizriyani; Ismatul Khasanah (LLDIKTI Wilayah X, 2023)
This study aims to reveal the form and meaning of registers, as well as the importance and function of using registers of journalist community in Malang Raya. Researcher used the questionnaire method and tapping and note-taking techniques to collect data. Intralingual and extralingual equivalent methods were used by researchers to analyze the data. The result of this study indicates that there are 32 registers found in journalist community in Malang Raya. These registers have lexical meaning according to the language dictionary and cultural meaning according to the social context in the journalist communityp in Malang Raya. Most journalists in Malang Raya consider it important to use the register in their journalistic activities because it functions as a way of interacting and communicating with others. Then it also functions as a differentiator with community groups in general.